1, 25-Dihydroxyvitamin D Protects Intestinal Epithelial Barrier by Regulating the Myosin Light Chain Kinase Signaling Pathway. Issue 11 (November 2015) - Du, Jie; Chen, Yunzi; Shi, Yongyan; Liu, Tianjing; Cao, Yong; Tang, Yue; Ge, Xin; Nie, Hongguang; Zheng, Changqing; Li, Yan Chun
Abstract : Background: The myosin light chain kinase (MLCK) pathway controls intestinal epithelial barrier permeability by regulating the tight junction. 1, 25-dihydroxyvitamin D (1, 25(OH)2 D3 )-vitamin D receptor (VDR) signaling protects the epithelial barrier, but the molecular mechanism is incompletely understood. Methods: MLCK activation and barrier permeability were studied using monolayers of HCT116, Caco-2, and SW480 cells treated with tissue necrosis factor α with or without 1, 25(OH)2 D3 . The MLCK pathway was analyzed in normal and inflamed colonic biopsies from patients with ulcerative colitis. Colonic mucosal barrier permeability and MLCK activation were also investigated using trinitrobenzene sulfonic acid–induced colitis models in vitamin D analog paricalcitol-treated wild-type mice and mice carrying VDR deletion in colonic epithelial cells. Results: Tissue necrosis factor α increased cell monolayer permeability and induced long isoform of MLCK expression and myosin II regulatory light chain (MLC) phosphorylation, and 1, 25(OH)2 D3 blocked tissue necrosis factor α–induced increases in monolayer permeability and MLCK-MLC pathway activation by a VDR-dependent fashion. 1, 25(OH)2 D3 directly suppressed long MLCK expression by attenuating NF-κB activation, and chromatin immunoprecipitation assays confirmed that 1, 25(OH)2 D3 disrupted p65 binding to 3 κB sites in long MLCK gene promoter. In human ulcerative colitis biopsies, VDR reduction was associated with increases in long MLCK expression and MLC phosphorylation. In trinitrobenzene sulfonic acid colitis models, paricalcitol ameliorated colitis, attenuated the increase in mucosal barrier permeability, and inhibited long MLCK induction and MLC phosphorylation. In contrast, mice with colonic epithelial VDR deletion exhibited more robust increases in mucosal barrier permeability and MLCK activation compared with wild-type mice. Conclusions: These data demonstrate that 1, 25(OH)2 D3 -VDR signaling preserves the mucosal barrier integrity by abrogating MLCK-dependent tight junction dysregulation during colonic inflammation. Abstract : Article first published online 17 August 2015.Supplemental Digital Content is Available in the Text.